Radiochromic film dosimetry for VHEE and UHDR: protocol adaptation and verification at the CLEAR facility - Rieker, Vilde F.; Bateman, Joseph J.; Wroe, Laurence; Caloz, Misael; Grilj, Veljko; Aguiar, Ygor Q.; Schüller, Andreas; Bailat, Claude; Farabolini, Wilfrid; Gilardi, Antonio; Robertson, Cameron; Korysko, Pierre; et al. (Frontiers in Physics, 2025)
Radiochromic films (RCFs) offer effective two-dimensional dosimetry with a simple, low-cost operating principle, making them suitable for very high-energy electron (VHEE) and ultra-high dose rate (UHDR) applications, where dosimetry standards are lacking. However, achieving high-accuracy measurements with RCFs presents significant challenges, especially in the absence of standardised protocols. To ensure reliable and comparable outcomes, adapted protocols based on a thorough understanding of RCF behaviour are essential. Despite over 6,000 publications addressing RCF protocols, comprehensive guides for high-throughput research machines with small, non-uniform beams are scarce. This paper aims to be a comprehensive guide for non-expert users of RCFs, particularly in VHEE and UHDR research. We identify common errors in RCF preparation, scanning, and processing, proposing strategies to enhance accuracy and efficiency. Using our optimised RCF protocol at the CLEAR facility, we demonstrate a 5% agreement compared to alanine dosimeters irradiated with Gaussian VHEE beams, establishing this protocol as a solid foundation for reliable dosimetry in advanced radiotherapy research.